FACTORS INFLUENCING THE WELFARE OF RAJUANGAN FISHERMEN IN THE EASTERN COASTAL WATERS OF LAMPUNG PROVINCE - Nopendi, Gusti Putu; Yudha, Indra Gumay; Endaryanto, Teguh; Rochana, Erna; Abidin, Zainal (Jurnal Perikanan Unram, 2025)
The objective of this study is to identify the factors influencing the welfare of blue swimming crab fishermen in the eastern coastal region of Lampung Province. The study was conducted in three regencies: East Lampung, Central Lampung, and Tulang Bawang, with a sample of 100 blue swimming crab fishermen. Daily fishermen use boats with a capacity of 1-2 GT, while babangan fishermen use boats with a capacity of more than 2 GT. The average catch for daily fishermen ranges from 1.99 to 3.18 kg per trip during the east season and from 9.08 to 10.33 kg per trip during the west season. Babangan fishermen catch an average of 74 kg per trip during the east season and 222 kg per trip during the west season. The factors influencing the welfare of fishermen during the east season are income level (X1), number of family dependents (X4), housing conditions (D1), ease of access to education (D3), and ease of access to transportation (D4). During the west season, the influencing factors are income level (X1), education level (X3), number of family dependents (X4), age of the head of the family (X5), ease of access to healthcare services (D2), and ease of access to education (D3).